Waiting for the wave: Political leadership, policy windows, and alcohol policy change in Ireland - Lesch, Matthew (Soc Sci Med, 2021)
Existing research has identified numerous barriers to the adoption of public health policies for alcohol, including the cross-cutting nature of the policy problem and industry influence. Recent developments in Ireland suggest that while formidable, such barriers can be overcome. Ireland's 2018 alcohol legislation adopts key evidence-based measures, introducing pricing, availability and marketing regulations that are world-leading in public health terms. Drawing primarily on the Multiple Streams Approach (MSA), this study investigates the adoption of the Public Health (Alcohol) Act 2018. We draw data from 20 semi-structured interviews with politicians, government advisors, public health experts, and advocates, as well as from relevant primary documents, newspaper articles, and other material in the public domain. We find that increased public attention to alcohol-related harms in Ireland (problem stream), developments within the institutional location of policymaking (the policy stream), and the political pressure exerted by politicians and advocates (the political stream) all combined to open a policy window. Unlike previous alcohol policy reform efforts in Ireland, several personally committed and well-positioned leaders championed policy change. This study suggests that political leadership might be important in understanding why public health approaches to alcohol have been embraced in some contexts but not in others.